2006
DOI: 10.1080/08120090500434609
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature (<110°C) thermal history of the Mt Isa and Murphy Inliers, northeast Australia: evidence from apatite fission track thermochronology *

Abstract: The paucity of Phanerozoic rock sequences in the Proterozoic Mt Isa and Murphy Inliers in northern Australia renders it difficult to determine their Phanerozoic tectonic histories. However, thermochronological methods provide a means to assess this problem. Apatite fission track ages vary from 390 to 218 Ma, and mean track lengths range between 11.1 and 13.6 mm. These results record a non-linear cooling history below about 110 + 108C. Forward modelling of the fission track data suggests that the first episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…390–300 Ma which are much slower than those typically observed in uplifted or incised terrains, but higher than for quiescent cratonic regimes (e.g., Fairbridge & Finkl, 1980; Summerfield & Hulton, 1994). Given these slow cooling rates, the samples from the central McArthur Basin appear to have not been significantly influenced by the Alice Springs Orogeny, and contrast with many thermal history profiles documented across northern Australia (e.g., Glorie, Agostino, et al, 2017; Nixon, Glorie, Collins, Whelan, et al, 2021; Spikings et al, 2006). Instead, we attribute Devonian–Carboniferous cooling in the central McArthur Basin to gradual erosion of overlying sediments and volcanics of the Georgina Basin and Kalkarindji LIP, which are now only sparsely preserved within the McArthur Basin region (Abbott et al, 2001; Ahmad & Munson, 2013; Dunn, 1963; Glass & Phillips, 2006).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…390–300 Ma which are much slower than those typically observed in uplifted or incised terrains, but higher than for quiescent cratonic regimes (e.g., Fairbridge & Finkl, 1980; Summerfield & Hulton, 1994). Given these slow cooling rates, the samples from the central McArthur Basin appear to have not been significantly influenced by the Alice Springs Orogeny, and contrast with many thermal history profiles documented across northern Australia (e.g., Glorie, Agostino, et al, 2017; Nixon, Glorie, Collins, Whelan, et al, 2021; Spikings et al, 2006). Instead, we attribute Devonian–Carboniferous cooling in the central McArthur Basin to gradual erosion of overlying sediments and volcanics of the Georgina Basin and Kalkarindji LIP, which are now only sparsely preserved within the McArthur Basin region (Abbott et al, 2001; Ahmad & Munson, 2013; Dunn, 1963; Glass & Phillips, 2006).…”
Section: Discussionmentioning
confidence: 79%
“…Instead, we attribute Devonian–Carboniferous cooling in the central McArthur Basin to gradual erosion of overlying sediments and volcanics of the Georgina Basin and Kalkarindji LIP, which are now only sparsely preserved within the McArthur Basin region (Abbott et al, 2001; Ahmad & Munson, 2013; Dunn, 1963; Glass & Phillips, 2006). Unlike major structural reactivation observed in the adjacent Pine Creek Orogen and Murphy Province (Nixon, Glorie, Collins, Whelan, et al, 2021; Spikings et al, 2006), any Devonian–Carboniferous deformation in the McArthur Basin appears to have been minor, at most serving to elevate the region above the peritidal to shallow marine conditions experienced during Georgina Basin deposition (Kruse & Radke, 2008) and into subaerial exposure, without the creation of meaningful topographic relief.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Low-temperature data from the eastern Murphy Province presented by Spikings et al (2006) suggests cooling in this region persisted for notably longer than that observed in the western Murphy Province. Cooling in the eastern Murphy Province continued through ca.…”
Section: Permian-triassicmentioning
confidence: 88%
“…Permian cooling is additionally preserved further east in the Palaeoproterozoic Mount Isa Inlier, at the eastern edge of the NAC (Spikings et al., 1997). This younger cooling progression is most likely linked to the inboard propagation of strain during the later stages of the Tasmanide accretion at the east Australian margin (Spikings et al., 1997, 2006), most likely during the Lachlan Orogeny and Hunter‐Bowen Orogeny (e.g., Glen et al., 2009; Jessop et al., 2019; Rosenbaum, 2018). It is, however, notable that the exposed eastern Murphy Province appears to display elevated heat production (Figures 6a and 6c) corresponding to an elevated geothermal gradient estimated at ∼33°C/km (Supporting Information ), causing the lithosphere to become thermally weakened.…”
Section: Discussionmentioning
confidence: 99%